Summary of the 2023 (1st edition) Report of TCEP (Tracking Clean Energy Progress) by the International Energy Agency (IEA), and Proposed Process for Computing a Single Aggregate Rating - Marzouk Osama A. (E3S Web of Conferences)
We provide a summary of the progress of all the 53 assessed components describing the global alignment with the Net Zero Emissions by 2050 Scenario (NZE) of the International Energy Agency (IEA), with an intermediate trajectory scope of 2030. The 53 components (grouped in eight categories) cover sectors (such as Transport, and Buildings), subsectors (such as Aviation, and Building Envelopes), technologies (such as Biofuels, and Electrification), infrastructure and cross-cutting strategies (such as CO2 Transport and Storage, and Electrolyzers). For each component, IEA assigned one of three qualitative progress levels; namely “On track”, “More efforts needed”, or “Not on track”. The IEA’s assessment results were made publicly available in the form of an online web-based report, titled “Tracking Clean Energy Progress”, or TCEP, which was published on 12/July/2023. Out of the TCEP’s 53 assessed components, only three were rated as “On track”, and these are (1) Solar Photovoltaic (PV), (2) Electric Vehicles (EV), and (3) Building Lighting. For the remaining 50 assessed components of TCEP; 28 were rated as “More efforts needed”, and 22 were rated as “Not on track”. We propose a quantitative aggregate numerical score to describe the overall progress in the global clean energy transition as reflected by the TCEP components, and we compute it as 2.23/4 (or 55.7%). Finally, we present selected historical records (based on IEA data) about the three satisfactory components of TCEP for the global clean energy transition.